2019
DOI: 10.1002/jsfa.9875
|View full text |Cite
|
Sign up to set email alerts
|

Innovative perspectives on Pulicaria dysenterica extracts: phyto‐pharmaceutical properties, chemical characterization and multivariate analysis

Abstract: BACKGROUND In this study, we aimed to evaluate the influence of different extraction procedures [decoction, homogenizer‐assisted extraction (HAE), infusion, maceration, Soxhlet and ultrasound‐assisted extraction (UAE)] on the chemical profiling and biological properties of methanol and water extracts of Pulicaria dysenterica (L.) Bernh. The chemical profiles of the extracts were evaluated by high‐performance liquid chromatography coupled to electrospray ionization and time‐of‐flight mass spectrometry (HPLC‐ESI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…It is observed that apart from extraction methods, the types of solvents equally influenced the chemical composition of the extracts, as only solvents of the same polarity with the solutes (phytochemicals) will eventually dissolve the solutes. Such outcomes are in accordance with several other studies stating HAE using methanol as an efficient extraction technique in extracting high yield of biogenic substances [19–23] …”
Section: Resultssupporting
confidence: 93%
“…It is observed that apart from extraction methods, the types of solvents equally influenced the chemical composition of the extracts, as only solvents of the same polarity with the solutes (phytochemicals) will eventually dissolve the solutes. Such outcomes are in accordance with several other studies stating HAE using methanol as an efficient extraction technique in extracting high yield of biogenic substances [19–23] …”
Section: Resultssupporting
confidence: 93%
“…Traditionally, ME and SOXE are widely applied to extract plant components from natural products [ 37 ]. However, they are time-consuming, labor-intensive, require large amounts of extraction solvents and have low extraction yield [ 38 , 39 ]. Therefore, in this case, nonconventional extraction techniques can be applied to extract phytochemical components from natural products [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…• Pulicaria dysenterica is to be found usually on wet and mildly saline soils [57] and is known for chemicals contained in its oils [58,59]. In the Czech Republic, it is scattered only across the valleys in southern Moravia and can be rarely seen in the White Carpathians, in Haná region, or the Moravian Gate and Ostrava regions [60].…”
Section: Appendix Bmentioning
confidence: 99%